Freedom to provide services in the European Union and environmental protection: liberalization versus public intervention - Pernas García, Juan José (Universidad Nacional del Litoral, 2014)
The article analyses the issue of freedom of provision of services in the European Union and the protection of the environment from the perspective of the impacts of the deregulatory process initiated by the services directive in environmental law, examining the tension between liberalization and public intervention in this matter.